2004
DOI: 10.1038/oby.2004.267
|View full text |Cite
|
Sign up to set email alerts
|

Physical Activity among African‐American Girls: The Role of Parents and the Home Environment

Abstract: ADKINS, SARAH, NANCY E. SHERWOOD, MARY

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
135
0
6

Year Published

2009
2009
2016
2016

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 140 publications
(149 citation statements)
references
References 30 publications
8
135
0
6
Order By: Relevance
“…Only a few studies have investigated these variables and they focused mainly on self-efficacy. These studies support the assumption that parents' self-efficacy is associated with children's weight related behavior, such as exercising (Adkins, Sherwood, Story, & Davis, 2004;Smith et al, 2010;Taveras, Mitchell, & Gortmaker, 2009). With respect to risk perception it might be important to consider whether parents evaluate their children's weight status correctly in the first place.…”
Section: Introductionsupporting
confidence: 49%
“…Only a few studies have investigated these variables and they focused mainly on self-efficacy. These studies support the assumption that parents' self-efficacy is associated with children's weight related behavior, such as exercising (Adkins, Sherwood, Story, & Davis, 2004;Smith et al, 2010;Taveras, Mitchell, & Gortmaker, 2009). With respect to risk perception it might be important to consider whether parents evaluate their children's weight status correctly in the first place.…”
Section: Introductionsupporting
confidence: 49%
“…Although parents have an important role to play in promoting children's PA [12,13], the extent of crossgroup similarities we observed suggests parental attitudes alone cannot account for differences in PA levels between ethnic groups. There is evidence to suggest a combination of cultural and environmental factors may limit the PA opportunities of ethnic minority children living in Western countries [14].…”
Section: Discussionmentioning
confidence: 67%
“…Influences on children's PA behaviours range from individual (e.g., children's preferences) to interpersonal (e.g., parental support), organisational (e.g., school PA provision) and environmental (e.g., local PA opportunities) levels and act either independently or synergistically to impact on children's behaviour [10,11]. At the interpersonal level, parents play an instrumental role in determining children's PA levels through their attitudes, parenting practices and own PA behaviours [12,13]. Cultural factors may influence how children's PA is perceived and supported by parents of different ethnic groups [14].…”
Section: Introductionmentioning
confidence: 99%
“…Other studies, however, have found contradictory findings on the association between environmental characteristics and physical activity (Ferreira et al, 2007). For example, one study found no link between the proximity of the park and physical activity (Adkins, 2004), and another study found no association between neighbourhood safety and physical activity (Sallis, 1999). These inconsistent findings need further exploration.…”
Section: Literature Reviewmentioning
confidence: 58%